The Impact of TikTok Political Campaigning on the Motivation of First-Time Voters in East Java among @khofifah.official Followers - Wahyuni, Nanda Dwi; Angelie, Therecia; Olivia, Meidhora (Journal Commedies, 2024)
This research aims to show how much influence political campaign content on TikTok has on the motivation of new voters in East Java who follow the @khofifah.official account. The object of this research is the motivation of new voters in East Java who follow the @khofifah.official TikTok account after seeing the political campaign content shared by Khofifah Indar Parawansa on her TikTok account. Where through the campaign content it is expected to influence the perception, attitude, and participation of new voters. This research also aims to analyze how the elements conveyed through Khofifah's social media account, such as messages, visuals, and interactions with voters, can increase their involvement in the election process. This research method uses a quantitative approach and data collection through surveys by distributing questionnaires online to 398 new voter respondents in East Java who follow the @khofifah.official account. The results of this research indicate that political campaign content on TikTok has a very significant influence on the motivation of new voters, with a contribution of 89.9%. The results of the simple linear regression test prove that the campaign content conveyed through TikTok has succeeded in influencing the motivation of new voters.